Novel thermostable clostridial strains through protoplast fusion for enhanced biobutanol production at higher temperature—preliminary study - Muhammad Ferhan; Yaser Dahman (AIMS Energy, 2016)
The objective of this study is to improve the thermal stability of clostridium strains for enhanced biobutanol production. Thermostable clostridia species were developed through protoplast fusion between mesophilic clostridial species (i.e., Clostridium beijerinckii and Clostridium acetobutylicum) and thermophilic clostridial species (i.e., Clostridium thermocellum). Production of biobutanol was examined in the present preliminary study using the clostridium strains and their protoplast fusants using sugar mixture with composition identical to that of wheat straw acid hydrolysate. Maximum biobutanol production of 9.4 g/L was achieved by a fused strain at 45 °C with total sugar consumption of 66% compared to that at 35 °C (i.e., 8.4 g/L production and 64% total sugar consumption). Glucose and xylose uptake rates were generally higher compared to all other individual sugars in the feedstock. In general, average cell concentrations were in close proximity for all parenting and fused strains at 35 °C; i.e., in the range of 5.12 × 107 to 5.49 × 107 cells/mL. Average cell concentration of fusants between the mesophilic clostridial species and the thermophilic clostridial species slightly increased to ~ 5.62 × 107 cells/mL at a higher temperature of 45 °C. These results, in addition to the ones obtained for the butanol production, demonstrate enhanced thermal stability of both fusants at a higher temperature (45 °C).